THE IMPACT OF GEOPOLITICAL UNCERTAINTY ON GLOBAL SUPPLY CHAIN RESILIENCE - Melyana R Pugu; Shinta Dzauharoh (Adisam Publisher, 2026)
This research explores the influence of geopolitical uncertainty on the resilience of global supply chains. Through the analysis of geopolitical events such as international conflicts, economic sanctions, trade policy changes, and political fluctuations, the research identifies the significant impact they have on the flow of goods and raw materials, which includes delivery delays, increased operational costs, and product scarcity in the market. The research also underscores the importance of global companies managing risks due to geopolitical uncertainties to keep their supply chains running smoothly. With risk management strategies that include supplier diversification, building inventory reserves, strengthening relationships with suppliers, utilising the latest technology, and developing comprehensive contingency plans, companies can increase resilience to geopolitical disruptions. The findings of this study confirm that a proactive and sustainable approach to risk management is essential to strengthen a company's competitiveness and operational resilience in the long term.